2022
DOI: 10.3390/sports10120189
|View full text |Cite
|
Sign up to set email alerts
|

Special Issue “Talent Identification and Development in Youth Sports”

Abstract: We are delighted to share our Special Issue on Talent Identification and Development in Youth Sports [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…And on the other hand, sports TAD is a strong support to stop inactivity-related diseases [ 39 ]. The purpose of TID has been studied by various scholars, including cultivating elite athletes [ 5 , 54 ], ensuring the success of professional clubs, national governing bodies [ 55 ], and identifying the most potential athletes [ 56 , 57 ]. It is crucial that the program's focus is on identifying players with long-term potential instead of just those who can win tournaments at present.…”
Section: Resultsmentioning
confidence: 99%
“…And on the other hand, sports TAD is a strong support to stop inactivity-related diseases [ 39 ]. The purpose of TID has been studied by various scholars, including cultivating elite athletes [ 5 , 54 ], ensuring the success of professional clubs, national governing bodies [ 55 ], and identifying the most potential athletes [ 56 , 57 ]. It is crucial that the program's focus is on identifying players with long-term potential instead of just those who can win tournaments at present.…”
Section: Resultsmentioning
confidence: 99%
“…To enhance the design of training tasks and facilitate continuous improvement among athletes, it is crucial to implement regular performance assessments. A study conducted with U13 female volleyball players demonstrated the effectiveness of adjusting the training focus based on a flexible periodization, tailored to players' assessments during four vs. four small-sided game (SSG) formats, creating a more encouraging learning environment (Loureiro et al, 17). In contrast, adhering to a rigid planning structure whereby adjustments were only made monthly failed to align with the learners' developmental needs.…”
Section: Knowledge Creationmentioning
confidence: 99%
“…For instance, the continuous performance assessment is critical for creating a conducive learning environment for young athletes. Accordingly, coaches should adjust training focus based on regular assessments by adopting a flexible periodization aligning with the developmental needs of players (17).…”
Section: From Knowledge To Actionmentioning
confidence: 99%
See 1 more Smart Citation